Implementing cooperative learning in physical education and sport to improve children fundamental movement skill - Tri Bayu Norito; Firmansyah Dlis; Achmad Sofyan Hanif; Muhammad Iqbal (Kazimierz Wielki University, 2019)
This study discusses Physical education and sport (PES) focusing on fundamental movement skill (FMS) learning. This FMS include locomotor , non locomotor dan manipulative for students of elementary school. The fact that students had not shown their development in FMS has been a concern for PES teachers. To overcome this problem, this study proposed cooperative learning (CL) method to improve students' FMS in locomotor, non-locomotor and manipulative movement. This study applied quasi-experimental method. There were 120 students who involved in this study and they were divided into two groups namely: the experimental and control group. The instrument used to collect data is a battery test of FMS. Based on the results of the t-test, the mean of pre-test FMS for the experimental group is 41.26 and for the post-test is 56.38. In the control group, students got average pre-test of FMS 46.14. and in post-test is 50.74. The results of this study shows that the application FMS learning based on CL improves students' achievement in FMS learning. To put this into practice, this study designed implementation to show practitioners FMS learning based on CL that can be used in learning locomotor, non-locomotor and manipulative movements.